Errores de medicación en la Unidad de Cuidados Intensivos - Salazar L., Nicole; Rojas A., Lorena; Jirón A., Marcela; Romero P., Carlos (Revista Hospital Clínico Universidad de Chile, 2012)
The safety and quality care are two attributes of the health care that are closely related. The critically ill patients are vulnerable to medical errors, and may experience preventable adverse events, often associated with drugs. The errors in the medication use process may occur at any stage, it is ordering, transcription, dispensing, preparation or administration. Medication errors (ME) can occur in one third of patients hospitalized in an ICU and have the potential to cause permanent damage to patients and longer hospital stay, with the resulting emotional and financial cost associated. Although technology can reduce the likelihood for adverse drug events, the optimal methods for implementation, integration, and evaluation in clinical practice remain unclear. In this paper we present some strategies and interventions to reduce the incidence of ME and optimize the safety and quality of care of critically ill patients.